Weed treaters. - Fleming, Sibley (American City & County, 2005)
Provides information on technologies and methods for weed management in the U.S. Use of aerial imagery taken with hyperspectral sensors in Bonneville County, Idaho; Background on the Weed Information Management System software released by the Nature Convervancy; Development of the National Early Detection and Rapid Response System for Invasive Plants for the Federal Interagncy Committee for the Management of Noxious and Exotic Weeds by the U.S. Bureau of Land Management.